2015
DOI: 10.1001/jamaneurol.2015.2742
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin D Levels With Multiple Sclerosis Activity and Progression in Patients Receiving Interferon Beta-1b

Abstract: IMPORTANCE Low serum 25-hydroxyvitamin D (25[OH]D) levels are associated with an increased risk of multiple sclerosis (MS) as well as with increased disease activity and rate of progression in clinically isolated syndromes and early MS. OBJECTIVE To assess the association between 25(OH)D and disease course and prognosis in patients with relapsing-remitting MS treated with interferon beta-1b. DESIGN, SETTING, AND PARTICIPANTS We conducted a prospective cohort study assessing 25(OH)D levels and subsequent MS dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
114
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(131 citation statements)
references
References 29 publications
9
114
0
3
Order By: Relevance
“…80,82 Furthermore, inverse correlations between 25(OH)D levels and the level of disability have been found. 70,79 These were not observed for disability progression (Muris et al unpublished data), 70,83 except for a study including only patients with clinically isolated syndrome. 84 Here a poor vitamin D status was associated with more cerebral lesion accumulation, more brain atrophy and more disability progression over time.…”
Section: The D In Development and Disease Coursementioning
confidence: 90%
“…80,82 Furthermore, inverse correlations between 25(OH)D levels and the level of disability have been found. 70,79 These were not observed for disability progression (Muris et al unpublished data), 70,83 except for a study including only patients with clinically isolated syndrome. 84 Here a poor vitamin D status was associated with more cerebral lesion accumulation, more brain atrophy and more disability progression over time.…”
Section: The D In Development and Disease Coursementioning
confidence: 90%
“…Thus, one study comprising 68 patients randomized to placebo or 20,000 IU vitamin D3 per week for 2 years were completely negative, although mean serum 25(OH)D more than doubled to 121 nmol/l in the intervention group [13]. Conversely, another study of comparable size showed a significant and pronounced effect of 14,000 IU vitamin D3 per week on new gadolinium-enhancing lesions after 1 year [14]. The first study included only clinical end points, and the pre-study relapse rate was only 0.11 [13].…”
Section: Can Vitamin D Reduce Inflammation In Relapsing-remitting Mulmentioning
confidence: 99%
“…Although negative correlations between disability and vitamin D status have been described in MS cohorts [42,59] , an effect of vitamin D status on disability progression was not found in longitudinal [60][61] and cross-sectional data [59] . Only at the start of disease, in clinically isolated syndrome (CIS) patients, a higher vitamin D status predicts less disability progression [53] .…”
mentioning
confidence: 99%
“…Furthermore, inverse correlations between 25(OH)D levels and the level of disability have been found [42,59] . The correlations were not observed for disability progression [59][60][61] , except for a study including only clinically isolated syndrome (CIS) patients [53] . Here a poor vitamin D status was associated with more cerebral lesion accumulation, more brain atrophy and more disability progression over time [53] .…”
mentioning
confidence: 99%
See 1 more Smart Citation